97.8k views
3 votes
How can you write (x-3)(x+4)-18 as a product of two binomials? Please show work please help

How can you write (x-3)(x+4)-18 as a product of two binomials? Please show work please-example-1

1 Answer

2 votes

Answer:

(b) (x-3)(x+4)-18 = (x+6)(x-5)

Explanation:

Here , the given expression is P(x) = (x-3)(x+4)-18

Simplifying the given expression ,we get:


(x-3)(x+4)-18 = x(x+4) -3(x+4) -18\\=x^2 + 4x-3x-12-18\\=x^2+x-30\\=x^2 +6x-5x-30\\=x(x+6)-5(x+6)\\=(x+6)(x-5)\\\implies (x-3)(x+4)-18 = (x+6)(x-5)

So,the given polynomial P(x) can also be written as (x+6)(x-5)

Hence, P(x) = (x-3)(x+4)-18 = (x+6)(x-5)

User Salem Ouerdani
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.